Workers, Managers, Productivity Kaizen in Developing Countries - Hosono, Akio; Page, John; Shimada, Go (Springer Nature, 2020)
This open access book provides a glimpse into the Japanese management technique known as "Kaizen," and the ways it has been disseminated around the developing world. The novelty of this book is three-fold: it provides a contextualized view of the mechanisms of initiatives implementing Kaizen in developing countries; compared with productivity studies, it places the relationship between workers and managers at the center of inquiry, reflecting the intent of SDG8 concerning decent work and economic growth; and it provides an overview of the heterogeneity of Kaizen in terms of geography and firm size. This book explores how improving management techniques can support firms' productivity and quality. Given its wide range of case studies from across Africa, Asia and Latin America, this book will be of value to scholars, policymakers and advocates of sustainable development alike.